SISTEM INFORMASI PENJUALAN BARANG PADA CV XYZ - Ery Hartati; Lisa Amelia (Universitas Katolik Musi Charitas, 2018)
The purpose of this thesis is to make the Application of Goods Sales CV. XYZ Palembang. The methodology used is iterative (iterative). With several stages of the planning stage, analysis by analyzing the existing problems in the company, this design stage designing the sistem so that problems can be overcome, and at the implementation stage of programming and application testing.The results to be achieved is expected to help CV. XYZ in managing data sales of goods so that sales transactions become more effective and efficient The conclusion is that with this application is expected to provide information, process data in computerized, This application can also minimize the time in calculating the cost of sales of goods and can facilitate in search of data items most sold quickly, accurate so that the sales process can run in accordance with the expected.